Measuring Road Roughness and Its Effects on User Cost and Comfort 1985
DOI: 10.1520/stp34598s
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Operating Costs Related to Operating Mode, Road Design, and Pavement Condition

Abstract: From 1979 through 1982 the Federal Highway Administration contracted with the Texas Research and Development Foundation to update vehicle operating cost tables. In this research five components of vehicle operating cost were studied, including fuel consumption, maintenance and repair, oil consumption, tire consumption, and depreciation. The approach used in this research was to identify the consumption involved for each of these parameters and then to price these components to obtain vehicle operating costs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
1
6
0
1
Order By: Relevance
“…Figure 17 agrees well with a study reported by Jones and Robinson (1986) which shows that truck operating costs will roughly double between IRI of 3 and 7 m/km. The tyre wear calculated yields an excellent linear correlation and Figure 18 agrees with findings of Zaniewski and Butler (1985) who showed that, between a road in good and very bad states, tyre costs increase by 182% for trucks and 316% for cars and small trucks.…”
Section: Verification By Iri -Impact Curvessupporting
confidence: 83%
See 2 more Smart Citations
“…Figure 17 agrees well with a study reported by Jones and Robinson (1986) which shows that truck operating costs will roughly double between IRI of 3 and 7 m/km. The tyre wear calculated yields an excellent linear correlation and Figure 18 agrees with findings of Zaniewski and Butler (1985) who showed that, between a road in good and very bad states, tyre costs increase by 182% for trucks and 316% for cars and small trucks.…”
Section: Verification By Iri -Impact Curvessupporting
confidence: 83%
“…Zaniewski and Butler (1985) showed that the increase in vehicle operating costs on a degraded road surface was 80 times greater than the cost of restoring the road. Many reports also link poor pavement quality to substantial consequences on vehicle wear (Rakheja et al 2001, Howe et al 2004, FAA 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners have long recognized that rough roads increase vehicle operating costs (Zaniewski and Butler 1985) and lead to more expensive road repairs (AASHTO 2009). Studies have also linked rough roads to motion sickness (Griffin 1990) National Road and Transport Research Institute 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Various evaluation criteria were used in the past to make investment decisions for proposed projects or evaluate past projects. These evaluation criteria include travel time, vehicle operating cost (VOC), safety, and economic efficiency ( 4 12 ). Other criteria were employed to assess transportation projects’ impacts on land use, the social and biological environments, economic development, asset resilience, aesthetics, air quality, water resources, and noise ( 6 , 13 – 21 ).…”
mentioning
confidence: 99%